Usefulness of the percentage of free prostatic specific antigen compared to prostatic specific antigen total for prostate cancer detection - Alpaca-Salvador , Hugo (2023)
Background: The determination of the specific prostate antigen is widely used in the early detection of prostate cancer; however, a limitation has been its relative lack of specificity where the quantification of some isoforms as their free fraction could improve discrimination with benign prostate disease. The objective of the study was to compare the diagnostic performance of the percentage of free prostate specific antigen and the total prostate specific antigen for the detection of prostate cancer. Material and Methods: A retrospective investigation of validity and comparison of diagnostic tests was carried out with a consecutive sample of 56 cases of prostatic adenocarcinoma and 161 controls with benign prostatic hyperplasia treated at Hospital III EsSalud Chimbote from November 2015 to February 2020. Results: The percentage of free prostate specific antigen presented an area under the curve (AUC) of 0.82 (95% CI: 0.75 – 0.89), an optimal cut-off of 20.0%, sensitivity of 95.0 %, specificity of 35.0% and diagnostic accuracy of 50.2%; compared to total prostate specific antigen, which obtained an AUC of 0.76 (95% CI: 0.69-0.83), sensitivity of 96.4%, specificity of 24.2%, and diagnostic accuracy of 42.86%. Conclusions: The percentage of free prostate specific antigen presented a moderate and higher diagnostic performance than the total prostate specific antigen for the detection of prostate cancer and could reduce the proportion of unnecessary biopsies by 35.0%.